Household clusters of SARS-CoV-2 Omicron subvariants contemporaneously sequenced from dogs and their owners - Francisco C. Ferreira; Lisa D. Auckland; Rachel E. Busselman; Edward Davila; Wendy Tang; Ailam Lim; Nathan Sarbo; Hayley D. Yaglom; Heather Centner; Heather L. Mead; Ying Tao; Juan Castro; et al. (mSphere)
ABSTRACT Monitoring the zoonotic potential of emerging SARS-CoV-2 variants in animals is a critical tool to protect public health. We conducted a longitudinal study in 47 households reporting people with COVID-19 in Texas from January to July 2022, during the first Omicron wave. We evaluated 105 people and 100 of their companion animals for SARS-CoV-2 infection at three sequential sampling events, starting 0–5 days after the first reported diagnosis of COVID-19 in the house. SARS-CoV-2 RNA was detected in 68% of people from 43 households; 95.5% of people had antibodies to SARS-CoV-2. Dogs were the only animal species positive by RT-qPCR (5.4%; 3/55), and their viral loads were consistently lower compared with those from household members. Additionally, infected dogs did not yield infectious virus. Clusters of Omicron BA.1.1, BA.2.3.4, and BA.5.1.1 in people, dogs, and a dog food bowl confirmed human-to-dog transmission within households, with no evidence of onward transmission from the infected dogs. Eleven dogs (n = 55) and two cats (n = 26) had neutralizing antibodies against SARS-CoV-2. Overall, infection was not associated with clinical signs in pets; only two animals that tested negative for SARS-CoV-2 were reported to be sick. Nearly one-third (30.2%) of households with active COVID-19 had pets exposed to SARS-CoV-2, similar to our pre-Omicron studies; however, the incidence of infection in cats was lower compared with pre-Omicron. These differences suggest that the zoonotic transmission dynamics in households may differ based on variants.IMPORTANCESARS-CoV-2 infects a broad diversity of mammals, with companion dogs and cats at risk of infection via close contact with infectious owners. Longitudinal studies sampling pets and their owners over time are essential to understanding within-household SARS-CoV-2 transmission dynamics. Our repeated sampling in households with people reporting COVID-19 found that 68% of the people in 43 households had active SARS-CoV-2 infection during at least one of the three sampling events. Although none of the 27 cats were positive, 3/55 dogs had active infections. Household clusters of three different Omicron subvariants were involved in these human-to-dog transmission events, and our data suggest reduced infection in pets during Omicron transmission compared with pre-Omicron waves. Protecting pets from SARS-CoV-2 infection remains important, as viral evolution can be accompanied by changes in the infectiousness of different hosts.